Multi Modal Detection of Alzheimer’s Disease Using Structural MRI Images - Tahir, Yusuf Suleiman (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2019)
Alzheimer's disease (AD) is the most prevalent case of dementia and a progressive brain disorder. It is an irreversible neurodegenerative disease characterized by a decrease in cognitive and memory functions that are ultimately sufficiently severe to interfere with ordinary operations. The disease has no cure, but the related symptoms are managed by many therapy alternatives. While current treatments cannot prevent Alzheimer's progression, early detection can momentarily assist slow down the deterioration of dementia symptoms and enhance the quality of life for people with Alzheimer's disease and their caregivers. With clinical and neuroimaging data, attempts were produced to use multiple classical machine learning algorithms to automatically diagnose this disease. More recently, in-depth learning methods have been introduced for this purpose due to their superior efficacy. In this thesis, we suggest the use of the brain's structural magnetic resonance image (sMRI), acquired from the ADNI database, to construct a model for detecting Alzheimer's disease based on a profound convolutional neural network (CNN) ensemble. The proposed method relies on initial categorization of the brain data into three different categories: the full brain, the grey matter and the white matter. Three separate CNN models are built for each of these data types based on a pretrained network called VGGNet. After training, the decision (i.e Alzheimer’s patient or Healthy Control) from each of the models are then combined using a simple majority vote to obtain a single, final decision. This approach will give better and more accurate predictions than the use of a single model. Keywords: Alzheimer’s disease, Structural MRI, CNN, VGGNet, machine learning, Deep learning, ensemble network.

ÖZ: Alzheimer hastalığı (AD), en sık görülen demans ve ilerleyici beyin hastalığı vakasıdır. Normal operasyonlara müdahale edebilecek kadar şiddetli bilişsel ve hafıza fonksiyonlarında azalma ile karakterize geri dönüşümsüz bir nörodejeneratif hastalıktır. Hastalığın tedavisi yoktur, ancak ilgili semptomlar birçok terapi alternatifi tarafından yönetilir. Mevcut tedaviler Alzheimer'ın ilerlemesini engelleyemezken, erken teşhis, demansın bozulmasını yavaşlatmaya hemen yardımcı olabilir ve Alzheimer hastalığı olan kişiler ve bakıcıları için yaşam kalitesini iyileştirebilir. Klinik ve nörogörüntüleme verileriyle, bu hastalığı otomatik olarak teşhis etmek için çoklu klasik makine öğrenme algoritmaları kullanmaya çalışılmaktadır. Daha yakın zamanlarda, bu amaç için üstün etkinliklerinden dolayı derin öğrenme yöntemleri geliştirilmiştir. Bu çalışmada, evrişimli sinir ağı (CNN) tabanlı Alzheimer hastalığını saptamak için bir model oluşturmak üzere ADNI veri tabanından elde edilen beynin yapısal manyetik rezonans görüntülerinin (sMRI) kullanılması önerilmektedir. Önerilen yöntem, beyin verilerinin üç farklı maddede sınıflandırılmasına dayanmaktadır: tam beyin, gri madde ve beyaz madde. Bu çerçevede VGGNet adlı önceden belirlenmiş bir ağa dayanarak bu veri türlerinin her biri için üç ayrı CNN modeli oluşturulmuştur. Eğitimden sonra, modellerin her birinden alınan karar (örneğin AD veya HC), daha sonra tek bir nihai karar almak için basit çoğunluk oyu kullanılarak birleştirilmiştir. Bu yaklaşım, tek bir modelin kullanılmasından daha iyi ve daha doğru tahminlerde bulunmaktadır. Anahtar Kelimeler: Alzheimer hastalığı, Yapısal MRG, CNN, VGGNet, makine öğrenmesi, Derin öğrenme, topluluk ağı.
Master of Science in Electrical and Electronic Engineering. Thesis (M.S.) - Eastern Mediterranean University, Faculty of Engineering, Dept. of Electrical and Electronic Engineering, 2019. Supervisor: Prof. Dr. Hasan Demirel.
Keywords: Electrical and Electronic Engineering; Magnetic resonance imaging; Image Processing; Alzheimer’s disease; Structural MRI; CNN; VGGNet; machine learning; Deep learning; ensemble network